Challenges and Future Prospects of Using Biochar for Soil Remediation - Primus, Audrey; Marculescu, Alexandru; Cao, Linh Thi Thuy; Nadifah, Gina; Twum-Ampofo, Daniel; Jannat, Md Abu Hanifa; Tongco, Jovale Vincent (Tecno Scientifica Publishing, 2025)
Biochar gained significant attention as an eco-friendly and effective solution for remediating contaminated soils, particularly those impacted by pharmaceutical persistent pollutants (PPPs). These pollutants, known for their resistance to natural degradation and tendency to accumulate in soil, posed serious risks to both human health and ecosystems. To address this issue, researchers proposed the use of biochar as a remediation technology to remove PPPs through adsorption. As an efficient sorbent, biochar demonstrated the ability to immobilize pharmaceuticals in contaminated soils, thereby reducing their bioavailability and mobility, and ultimately mitigating their environmental impact. This review aimed to provide a comprehensive overview of the current understanding of PPPs contamination and the potential of biochar for remediation. It first summarized the occurrence of pharmaceutical pollutants in various countries and identified their primary sources. It then examined the environmental fate of these pollutants and outlined the key challenges associated with their management. The mechanisms by which biochar adsorbed pharmaceutical compounds were discussed in detail, followed by a case study that illustrated the effectiveness of this technology in practical applications. This review also evaluated the advantages and disadvantages of using biochar for remediation, along with the practical challenges encountered during its implementation. Future directions highlighted included developing methods for extracting toxic residues and enhancing the performance of biochar through chemical or structural modifications.